Clinical evaluation of the short-term effects of Cordyceps cicadae mycelium in lowering intraocular pressure. (August 2022) - Hsu, Jui-Hsia; Chang, Wen-Jui; Fu, Hsin-I; Chang, Han-Hsin; Chen, Chin-Chu
Graphical abstract: Highlights: First clinical report indicating the use of C. cicadae mycelium in the human eye. C. cicadae mycelium decreases IOP significantly within a short time. Optimal results were observed in female and elder groups. Submerge-cultured Cordyceps cicadae mycelium is safe for human use. Abstract: Cordyceps cicadae mycelium (CCM) reduces high intraocular pressure (IOP) in animal models. This clinical study determined the decrease in IOP after one CCM dose in humans. Forty-six patients with IOP ≥ 21 mmHg in either eye were enrolled and their pulse, blood pressure (BP), and IOP were assessed at 0 and 90 min after CCM administration. CCM did not affect the pulse, but it lowered systolic and diastolic BP overall at 90 min, particularly in men. CCM significantly reduced the IOP in patients IOP ≥ 21 mmHg in left and right eyes in overall, and women had a significant reduction compared with men. The IOP decrease in patients ≥ 60 years old showed a significant decrease in the left eye overall and in women, but the right eye showed only a minor decrease at 90 min. This is the first report indicating that CCM can quickly and significantly reduce high IOP in humans.